Efficacy of a commercial vaccine against different strains of rabbit haemorrhagic disease virus. Issue 7 (July 2017) - Read, AJ; Kirkland, PD
Abstract : Background: This study investigated the ability of a commercial rabbit haemorrhagic disease virus (RHDV) vaccine (Cylap®) to protect rabbits from disease caused by two different strains of the virus (v351 and K5) that are used or proposed to be used for wild rabbit control in Australia. These strains of the RHDV1 genotype belong to the 'classical RHDV' and 'antigenic variant RHDVa' subtypes, respectively. Methods: Vaccinated rabbits were exposed to very high doses of the virus either by direct oral dosing or by exposure to infected rabbit livers. Results & Conclusion: All vaccinated rabbits were protected against rabbit haemorrhagic disease, indicating that the Cylap® vaccine is effective against both strains of the virus under experimental conditions.